FORENSIC RECOVERY ANALYSIS OF LOST RAID 0 CONFIGURATION ON NETWORK ATTACHED STORAGE AS EVIDENCE IN COURT - Prawira, Dani; Nugraha, Beny; Marzuki , Marza Ihsan (Informatika, Universitas Jenderal Soedirman, 2023)
In the modern world of globalization, Digital Forensic science has emerged as a pivotal investigative tool for solving complex cases. This discipline proves particularly effective in deciphering digital evidence. In this study, we ventured to examine a Network Area Storage (NAS) device, specifically one containing three hard disks. Our objective was to validate that the Hash value generated before the duplication process matches identically with the Hash value post-imaging or duplication. Our findings demonstrate that through reconfiguration and recovery of RAID 0, previously deleted files can be restored using the methods outlined in our research. In essence, this study establishes that: (1) Reconstruction of RAID configurations is feasible, (2) Recovery of deleted files from a RAID 0 system is achievable, and (3) Such restored data can serve as admissible evidence in court.